From Waste to Resource: Use of Lemna minor L. as Unconventional Fertilizer for Lettuce (Lactuca sativa L.) - Ada Baldi; Leonardo Verdi; Lorenzo Piacenti; Anna Lenzi (Horticulturae)
Duckweeds, such as Lemna minor L., are invasive aquatic species that can proliferate on the surface of the nutrient solution in hydroponic systems, requiring removal operations from the cultivation tanks and disposal as waste. Several studies have demonstrated the potential use of duckweeds as an organic fertilizer. Recycling plant waste as a nutrient source for crops may be a circular approach to enhancing the sustainability of intensive horticultural production systems. Two pot experiments were carried out to evaluate the possibility of using the biomass of Lemna as a fertilizer for lettuce. The following fertilization treatments were applied: Control (no fertilization), Lemna biomass (60, 120, and 180 kg ha−1 nitrogen), urea (60 kg ha−1 nitrogen), and commercial organic fertilizer (60 kg ha−1 nitrogen). Lettuce head diameter, fresh and dry weight, the number of leaves, and the contents of minerals, nitrates, chlorophyll and carotenoids were determined. In addition, nitrogen use efficiency was calculated. Fertilization with Lemna resulted in a significant increase in yield compared to control (+50% considering the average of the three Lemna doses) and both inorganic (+65%) and organic (+71%) fertilization treatments. No differences in yield and quality were observed between the three doses of Lemna, but the lowest one was the treatment with the best performance in terms of N productivity. These results suggest that Lemna biomass may be a proper source of nutrients for lettuce with advantages for yield and no effect on quality. Therefore, its use as an alternative to commercial fertilizers can allow farmers to profitably exploit a waste product and, at the same time, reduce the costs for fertilization, thus achieving environmental and economic benefits.